KREATIVITAS, PEMACU DAN PENGHAMBATNYA DALAM KEHIDUPAN MANUSIA - Ru'iya, Sutipyo (Universitas Ahmad Dahlan, 2014)
Creativity is the most important part of the human being, therefore it is worth to look for what causes that can improve and what the cause of the inhibitors. Creativity can bring one's life into existence. Creativity is a thing that can always be developed in a person's life. One's creativity can be enhanced with a lot of things. One is coriusity (curiosity) which has a very large role in improving it. Harlock said that the cause of the inefficacy of creativity is a limitation of exploration, timing is too tight, encouragement family togetherness, limiting delusion, providing tools play a very structured, conservative attitudes of parents, parents were overprotective.